Pembentukan Portofolio Optimal Menggunakan Metode Optimasi Multiobjektif pada Saham di Bursa Efek Indonesia - Doni Rahmat Septiano; Syafriandi Syafriand; Media Rosha (Journal of Mathematics UNP, 2019)
Abstract –Multi-objective optimization is a method of formation of the portfolio was conducted in a way to maximize the level of expected return and risk of the portfolio at the same time with different weighting coefficients k value that states how much risk was taken. The purpose of this research is to form the optimal portfolio based on the properties of the investor. This research was based on LQ-45 stocks case studies in the period trading from February-July 2015. The optimal portfolio for risk seeker investors is when  with expected return at 0.18674% and the shares was invested only one stocks. At the risk indifference investors, the portfolio was formed when  in which the invested shares were nine stocks. The expected return rate was 0.11463% to 0.17998%. As of risk-averse investors, a portfolio was formed when  with invested stocks were ten stocks with expected return at 0.10837%. Keywords –return, expected return, risk, multi-objective optimization, portfolio